Teachers' perceptions and experiences of continuing professional development (CPD): opportunities and needs in Hong Kong primary schools - Wan, Wai-Yan Sally (2011)
The aim of this study was to explore teachers’ perceptions of continuing professional development in Hong Kong, focusing on teachers’ perceptions of CPD activities and teacher competencies in the Teacher Competencies Framework (TCF) in the latest government CPD policy, “Towards a Learning Profession: The Teacher Competencies Framework and the Continuing Professional Development of Teachers” (hereafter as “CPD Document 2003), as well as their perceptions about facilitating and inhibiting factors affecting CPD. In order to accomplish these purposes, one central research question was created: What are teachers’ perceptions of CPD activities and their professional development needs and what factors affect their CPD participation?